Transcending the numbers: the ethical role of the public accountant in sustainable and socially responsible education. - ROMERO-BELLO, Luisa Fernanda; Freyle, Eduard José Ramírez; Alfonso, Rafael Humberto Pinzón; Sarchi, Leidy Johanna Bastidas (Journal of Posthumanism, 2025)
This experimental study examined the social representations of financial accountants in their expert work. In particular, the quantitative study examined the attitudes and determination of responsible and socially responsible schooling among students, teachers and public accounting professionals. The results show that accountants consider their academic acquaintances as experts who perform their duties in accordance with social duty and ethical standards, which contribute to improving their professional and academic life.